2021
DOI: 10.3343/alm.2021.41.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Plasma NGAL:Hepcidin-25 for Major Adverse Kidney Events After Cardiac Surgery with Cardiopulmonary Bypass: A Pilot Study

Abstract: Background Neutrophil gelatinase-associated lipocalin (NGAL) and hepcidin-25 are involved in catalytic iron-related kidney injury after cardiac surgery with cardiopulmonary bypass. We explored the predictive value of plasma NGAL, plasma hepcidin-25, and the plasma NGAL:hepcidin-25 ratio for major adverse kidney events (MAKE) after cardiac surgery. Methods We compared the predictive value of plasma NGAL, hepcidin-25, and plasma NGAL:hepcidin-25 with that of serum creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…Nevertheless, the internal validity of our findings is strengthened by the similarities in risk variability within two independent, well-defined cardiac surgery cohorts with a consequent timing of biomarker sampling. We do not preclude the conclusion that other biomarkers for AKI risk prediction may also be affected by changing biomarker threshold selections [39].…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, the internal validity of our findings is strengthened by the similarities in risk variability within two independent, well-defined cardiac surgery cohorts with a consequent timing of biomarker sampling. We do not preclude the conclusion that other biomarkers for AKI risk prediction may also be affected by changing biomarker threshold selections [39].…”
Section: Discussionmentioning
confidence: 89%
“…This may possibly indicate a nephroprotective property through the interaction with reactive iron compounds since hepcidin-25 synthesis is physiologically increased by iron overload [ 6 ]. In our study cohort, this pattern of higher hepcidin-25 levels in patients without AKI described for urine samples ( P = 0.001 for 6 h and 24 h) [ 5 ] could not be demonstrated in patients’ plasma samples at 6 h and even less so at 24 h after CS with P = 0.189 and P = 0.652, respectively ( Figure 1 ) [ 2 ]. This is of interest as it may suggest that urinary biomarkers might be more sensitive for histological damage (i.e., tubular injury) than plasma biomarkers.…”
mentioning
confidence: 77%
“…In a recent study, we compared the predictive value of plasma Neutrophil Gelatinase–Associated Lipocalin (NGAL), hepcidin-25, and plasma NGAL:hepcidin-25-ratio with that of serum creatinine and urinary output for primary-endpoint MAKE (acute kidney injury [AKI] stages 2 and 3, persistent AKI >48 h, acute dialysis, and in-hospital mortality) and secondary-endpoint AKI in 100 on-pump CS patients at intensive care unit (ICU) admission (corresponding to 6 h). We performed receiver operator characteristic (ROC) curve, logistic regression, and reclassification analyses [ 2 ]. Out of 100 patients, 9 developed MAKE and 9 developed AKI, respectively.…”
mentioning
confidence: 99%
“…In this issue, Albert C, et al [ 4 ] reported that plasma NGAL:hepcidin-25 is a promising marker for predicting postoperative major adverse kidney events after cardiac surgery. In their previous study, considering laboratory and clinical availability of the biomarkers, they concluded that NGAL and interleukin-6 appear to be the most excellent candidates for implementation in kidney risk assessment [ 2 ].…”
mentioning
confidence: 99%
“…In this time, the authors newly presented the roles of plasma NGAL:hepcidin-25 in maintaining the homeostasis of labile-iron during and after cardiac surgery [ 4 ]. Consistent with recent reports showing changes of both urinary and plasma hepcidin-25 concentrations, their results also suggested that lower concentrations of hepcidin-25 are independently associated with increased mortality in critically ill patients with AKI requiring KRT [ 4 ].…”
mentioning
confidence: 99%